Rancang Bangun Aplikasi E-Perpustakaan SMP Negeri 31 Batam Dengan Metode Extreme Programming - Siti Novrianti; Saut Pintubipar Saragih (Universitas Putera Batam, 2026)
Library management at SMP Negeri 31 Batam was previously carried out manually using logbooks, which often caused data inaccuracies, delays in information retrieval, and difficulties in tracking book loans and inventory. This study aims to design and develop a web-based e-library application to improve the efficiency and accuracy of library administration. The system was developed using the Extreme Programming (XP) method, which emphasizes incremental development, user involvement, and flexibility in handling changing requirements. Data were collected through observation, interviews, and documentation to identify system requirements. The developed application provides features for managing book data, member registration, borrowing and returning transactions, recording damaged and lost books, book procurement, and automatic report generation. MySQL is used as the database to ensure structured and integrated data storage. The results indicate that the e-library system is able to accelerate administrative processes, reduce data recording errors, and improve the quality of library services for both students and librarians.